Properties of a certain subclass of starlike functions defined by a generalized operator - Yunus, Yuzaimi; Akbarally, Ajab Bai; Halim, Suzeini Abd (Academic Publications, 2018)
In this paper, we introduce the class Sα,λ n,s (β), consisting of analytic functions defined by a generalized operator. We derive coefficient inequalities, growth and distortion theorem, extreme points and Fekete-Szegö problem for functions in this class.